Stress in English and Tagalog a descriptive-contrastive analysis with suggested drill materials for first year student in the division of Rizal - Llagas, Avelina (Teston) 1930- (s.n.], 1971)
This research has two parts: Part I is a descriptive-contractive analysis of stress in English and Tagalog; Part II is composed of suggested drill materials for the teaching of English stress to the first year students in the Division of Rizal. The researcher made use of the structuralist's theory which expounds that the sound system of a language may be regarded as "set of rules which specify its pronunciation." In consonance with this linguistic theory, the data of stress in English and Tagalog were presented together with the formulas of stress patterns in both languages. The analysis was restricted to word stress, phrase stress, and sentence stress.